Uniting RNAi Technology and Conservation Biocontrol to Promote Global Food Security and Agrobiodiversity - Willow, Jonathan; Cook, Samantha M.; Veromann, Eve; Smagghe, Guy (Frontiers in Bioengineering and Biotechnology, 2022)
Habitat loss and fragmentation, and the effects of pesticides, contribute to biodiversity losses and unsustainable food production. Given the United Nation’s (UN’s) declaration of this decade as the UN Decade on Ecosystem Restoration, we advocate combining conservation biocontrol-enhancing practices with the use of RNA interference (RNAi) pesticide technology, the latter demonstrating remarkable target-specificity via double-stranded (ds)RNA’s sequence-specific mode of action. This specificity makes dsRNA a biosafe candidate for integration into the global conservation initiative. Our interdisciplinary perspective conforms to the UN’s declaration, and is facilitated by the Earth BioGenome Project, an effort valuable to RNAi development given its utility in providing whole-genome sequences, allowing identification of genetic targets in crop pests, and potentially relevant sequences in non-target organisms. Interdisciplinary studies bringing together biocontrol-enhancing techniques and RNAi are needed, and should be examined for various crop‒pest systems to address this global problem.